2003
DOI: 10.1590/s0100-879x2003001100009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stunned and infarcted canine myocardium by real time myocardial contrast echocardiography

Abstract: Differentiation between stunned and infarcted myocardium in the setting of acute ischemia is challenging. Real time myocardial contrast echocardiography allows the simultaneous assessment of myocardial perfusion and function. In the present study we evaluated infarcted and stunned myocardium in an experimental model using real time myocardial contrast echocardiography. Sixteen dogs underwent 180 min of coronary occlusion followed by reperfusion (infarct model) and seven other dogs were submitted to 20 min of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
(37 reference statements)
2
10
0
Order By: Relevance
“…In addition, in Groups I and II, MCE with the new technique did not find the infarct size, indicating that short coronary occlusion was not enough to produce myocardial infarction. The results were confirmed by TTC and consistent with previous studies showing that short occlusions in the myocardium (<45 min) followed by reperfusion resulted in myocardial stunning [3,4].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, in Groups I and II, MCE with the new technique did not find the infarct size, indicating that short coronary occlusion was not enough to produce myocardial infarction. The results were confirmed by TTC and consistent with previous studies showing that short occlusions in the myocardium (<45 min) followed by reperfusion resulted in myocardial stunning [3,4].…”
Section: Discussionsupporting
confidence: 91%
“…One possible explanation is that the presence of collateral flow from adjacent vascular beds allowing some degree of myocardial perfusion in the margins of regions supplied by the occluded coronary artery [4]. Although the risk area measured by color-coded map of the computer-aided software was also smaller than the anatomical risk area, the correlation between the above measurements was better than that between MPD and staining.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In recent years, myocardial contrast echocardiography has been demonstrated to be a feasible and accurate method for the evaluation of myocardial perfusion in many clinical settings (2)(3)(4)(5). In addition, the combination of intravenous contrast agents and RTMCE with application of high-mechanical index impulses for microbubble destruction followed by myocardial replenishment has permitted the quantification of myocardial blood flow (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The development of low-mechanical index imaging techniques that cause minimal microbubble destruction has permitted simultaneous analysis of myocardial perfusion and function in real time (2). Real-time myocardial contrast echocardiography (RTMCE) increases the sensitivity of dobutamine stress testing for the detection of coronary artery disease (3,4) and can distinguish between stunned and infarcted myocardium after acute ischemia (5). However, some concerns regarding the safety of this new imaging modality remain, mainly because some animal studies have demonstrated damage to the endothelial system in the presence of microbubbles and ultrasound (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%